Educator "What-Ifs": The Feasibility of Choice Making in the Classroom. (August 2017) - Jolivette, Kristine; Parks Ennis, Robin; Swoszowski, Nicole Cain
Educators who work with students with emotional and behavioral disorders may seek instructional strategies that are effective yet practical in the classroom. These strategies need a research base to support them and minimal time and/or effort to prepare or implement. One research-based option for educators across a variety of contexts is implementation of choice-making opportunities. This article offers suggestions for educators who may be hesitant to implement choice-making opportunities with students with challenging behaviors in instructional contexts.